"Green Altruism": Short Immersion in Natural Green Environments and Helping Behavior. (February 2016) - Guéguen, Nicolas; Stefan, Jordy
Research has consistently found exposure to a natural environment to be associated with health and psychological well-being. However, the effect of such an environment on social behavior and relationships remains in question. In a field experiment, male and female confederates accidentally dropped a glove on the ground while walking in a natural environment. The confederates continued walking, apparently unaware of their loss. Passersby were tested either before or after their immersion in an urban green park with large trees, lawns, and flowers. It was found that passersby tested after immersion in the park helped the confederates more readily than those tested before immersion in the park. In a second study, possible mediating factors of this effect (positive mood and desire to help others) were tested. Mood was found to be a mediating factor, whereas desire to help others partially mediated the relation between immersion in a natural environment and helping behavior.